Location in a Vertically Differentiated Industry - Emanuele Bacchiega; Antonio Minniti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
We analyze a two-stage game in a vertically differentiated duopoly with two regions which can differ for the willingness to pay of their consumers or for the market size; firms sequentially choose to settle in one region and then simultaneously compete in prices, selling their products both on the local market and on the foreigner one by exporting them at a fixed cost. We study how strategic interaction influences firms' location choices and we show that the decision whether to agglomerate or not crucially depends on the extent of regions' asymmetries, but, counter intuitively, there are parametric regions in which the model predicts that the leader (the first firm choosing location) settles either in the poorer or in the smaller region, leaving the other one to the follower. Welfare analysis completes the paper.
Keywords: 330; Betriebliche Standortwahl; Duopol; Interregionaler Handel; Theorie